2020
DOI: 10.1016/j.tibtech.2019.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Toward an Optimized Process for Clinical Manufacturing of CAR-Treg Cell Therapy

Abstract: Advances in the field of cell therapy have led to promising novel approaches to treat malignancies and other debilitating diseases. Redirecting the target antigen specificity of CAR-Treg cells represents one such promising approach.Current manufacturing processes for CAR-Tregs demonstrate challenges in cell purification, yield, expansion, CAR selection and gene delivery, supply chain, and quality control/product release testing.We propose a GMP-compatible manufacturing framework to enhance the CAR-Treg product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(52 citation statements)
references
References 104 publications
1
47
0
3
Order By: Relevance
“…We were able to show that GMP compliant production of nTreg products from patients with end stage renal disease who had several comorbidities is feasible, robust, and possible at reasonable costs (€17 500/product (£15 800; $20 500))-a prerequisite for trustworthy data from clinical adoptive cell treatment trials. [34][35][36] In line with the main trial objective, we also showed that infusion of autologous nTregs at the end of the first week after kidney transplantation was well tolerated. No evidence was found of cell infusion related short term or long term adverse effects, and we observed no signs of over immunosuppression.…”
Section: Discussionsupporting
confidence: 70%
“…We were able to show that GMP compliant production of nTreg products from patients with end stage renal disease who had several comorbidities is feasible, robust, and possible at reasonable costs (€17 500/product (£15 800; $20 500))-a prerequisite for trustworthy data from clinical adoptive cell treatment trials. [34][35][36] In line with the main trial objective, we also showed that infusion of autologous nTregs at the end of the first week after kidney transplantation was well tolerated. No evidence was found of cell infusion related short term or long term adverse effects, and we observed no signs of over immunosuppression.…”
Section: Discussionsupporting
confidence: 70%
“…258 Here, the authors confirmed that GvHD was less pronounced in mice that had received CXCR3-engineered Tregs than in mice that received nontransfected Tregs and that these genetically engineered Tregs mainly targeted and localized in the liver. 258 Furthermore, chimeric antigen receptor (CAR)-Tregs 259,260 provide an attractive option to optimize Treg stability and prevent exhaustion by the introduction of costimulatory molecules, such as CD28 or CD137/ 4-1BB. 260,261 The first CAR-Tregs contained an HLA-A2-specific CAR (A2-CAR) that was used to generate alloantigen-specific human Tregs.…”
Section: Tregs In Autoimmune Liver Diseasesmentioning
confidence: 99%
“…258 Furthermore, chimeric antigen receptor (CAR)-Tregs 259,260 provide an attractive option to optimize Treg stability and prevent exhaustion by the introduction of costimulatory molecules, such as CD28 or CD137/ 4-1BB. 260,261 The first CAR-Tregs contained an HLA-A2-specific CAR (A2-CAR) that was used to generate alloantigen-specific human Tregs. 259 Leving´s group demonstrated that in a mouse model of GvHD, engineered CAR-Tregs provided more effective immunosuppression than transferred polyclonal Tregs.…”
Section: Tregs In Autoimmune Liver Diseasesmentioning
confidence: 99%
“…Nach abgeschlossener Selektion erfolgt eine Aktivierung der Tregs, die häufig mit CD3- und CD28-Antikörper-Beads sowie über IL-2-Gabe durchgeführt wird [ 33 ]. Als Alternative wird die Aktivierung über letal bestrahlte, rekombinant antigenpräsentierende Zellen beschrieben.…”
Section: Herstellung Und Qualitätskontrolle Regulatorischer T-zellenunclassified
“…Letzteres gilt zwar auch für die Verwendung der Antikörper-Beads, insgesamt ist das mit ihrer Verwendung assoziierte Risikopotenzial für den Patienten allerdings als geringer einzuschätzen. Durch eine zusätzliche Gabe von Rapamycin lässt sich die selektive Depletion von T‑Effektorzellen erreichen und damit eine Instabilität der Tregs durch Expansion der T‑Effektorzellen verhindern [ 33 ].…”
Section: Herstellung Und Qualitätskontrolle Regulatorischer T-zellenunclassified